Paradox of (In)Visibility: Moving Beyond the Celebratory Rhetoric of Diversity - Wagner, Anne (Atlantis)

(untitled) (Mount Saint Vincent University, 2014)
This paper engages with issues of representation, voice, and presence/absence in feminist theorizing in the context of increasingly neo-liberal sites of higher education. Focusing on the dynamics of a largely racially homogenous student body, the analysis seeks to conceptualize how we may foster self-reflexivity in our practices when encouraging students to engage ethically with “difference.”